2018
DOI: 10.3390/genes9100513
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Causes Enhanced Secretion of YB-1 Protein that Restrains Proliferation of Receiving Cells

Abstract: The prototype cold-shock Y-box binding protein 1 (YB-1) is a multifunctional protein that regulates a variety of fundamental biological processes including cell proliferation and migration, DNA damage, matrix protein synthesis and chemotaxis. The plethora of functions assigned to YB-1 is strictly dependent on its subcellular localization. In resting cells, YB-1 localizes to cytoplasm where it is a component of messenger ribonucleoprotein particles. Under stress conditions, YB-1 contributes to the formation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 59 publications
2
26
0
Order By: Relevance
“…Similar to ArathEULS3, the secretion of hygromycin phosphatase and mannitol dehydrogenase was not mediated by any vesicular structures [45,46]. Interestingly, the mammalian Y-box protein YB-1 assembly in stress granules was recently associated with an enhancement of its unconventional secretion [47]. The YB-1 protein is involved in many fundamental biological processes and its localization highly depends on the conditions.…”
Section: Discussionmentioning
confidence: 96%
“…Similar to ArathEULS3, the secretion of hygromycin phosphatase and mannitol dehydrogenase was not mediated by any vesicular structures [45,46]. Interestingly, the mammalian Y-box protein YB-1 assembly in stress granules was recently associated with an enhancement of its unconventional secretion [47]. The YB-1 protein is involved in many fundamental biological processes and its localization highly depends on the conditions.…”
Section: Discussionmentioning
confidence: 96%
“…PABPC1 is a shuttle protein with predominantly cytoplasmic localization that binds to mRNA after its export from the nucleus [112]. Recently, it was found that PABPC1 accumulates in the nucleus upon YB-1 knockdown [113]. We speculate that YB-1 creates not only competitive conditions favorable for PABP functioning but also assists mRNP rearrangement in the nuclear pore.…”
Section: Yb Proteins In Translation Stimulationmentioning
confidence: 87%
“…In the majority of YB-1 secretion studies, the intracellular YB-1 level was not measured [198][199][200]. Only one study reports that under oxidative stress caused by sodium arsenite or H 2 O 2 treatment, YB-1 can secrete from the cell, and its intracellular concentration is slightly decreased [113]. Changes in the intracellular YB-1 content under oxidative stress and other stimuli are subject to further detailed investigation.…”
Section: Circanks1amentioning
confidence: 99%
“…and cyclin E 19 . In contrast, a role for an N-terminal 77 amino acid domain of YB-1 has been implicated in regulating progression of the G2/M phases of the cell cycle 20 and other studies have demonstrated that inhibiting YB-1 caused an arrest at G2/M 21,22 . Furthermore, prolonged exposure of breast cancer cells to YB-1 led to cytokinesis failure and slippage through the G1/S border 23 .…”
Section: Introductionmentioning
confidence: 99%